National Household Education Survey, 1996 ([Verlag nicht ermittelbar], 1998)
The National Household Education Survey (NHES) series reports information on the condition of education in the United States by collecting data at the household level rather than using a traditional school-based data collection system. The surveys attempt to address many current issues in education, such as preprimary education, school safety and discipline, adult education, and activities related to citizenship. This survey included two topical survey components: Parent/Family Involvement in Education (PFI) and Adult and Youth Civic Involvement (CI). The PFI component, which elicited information from parents and children aged 3 years through grade 12, focused on four areas: types and frequency of family involvement in children's schools, communication with teachers or other school personnel, children's homework and behavior, and learning activities with children outside of school. Other information collected for this component pertained to student experiences at school, children's personal and demographic characteristics, household characteristics, and children's health and disability status. The PFI information is provided in Part 1, Parent and Family Involvement in Education and Civic Involvement -- Parent Data. The CI component of the survey gathered information on civic participation, sources of information about government issues, and knowledge and attitudes about government. Items were administered to youths in grades 6 through 12 (Part 2, Youth Civic Involvement Data) and their parents, as well as to a representative sample of United States adults (Part 3, Adult Civic Involvement Data). The CI component also addressed opportunities for youth to develop personal responsibility and skills that would facilitate their taking an active role in civic life. CI questions were also asked of the parents surveyed in the PFI component, and these data also can be found in Part 1. In addition to the two major topical components, a screener component of the survey collected demographic and educational information on all members in every household contacted, regardless of whether anyone in the household was selected for an extended interview. (The term "extended interview" refers to the interviews completed in the topical components of the study, i.e., the Parent PFI/CI, the Youth CI, or the Adult CI interviews.) Items on the use of public libraries by the household were also administered in the screener portion for households without Parent PFI/CI extended interviews and in the first Parent PFI/CI interview in households in which one or more children were sampled. These data are presented in Part 4, Household and Library Data.